Evaluasi Kelayakan User Interface Prototype Aplikasi Mobile “HeartReco” Menggunakan System Usability Scale - Aji, Desak Ketut Puri Trisnantya; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Heart disease is a disease that can not be cured completely, so prevention and early management are needed to prevent the disease progression. Thus, dietary modification is an important factor that needs to be done for people with heart disease. HeartReco is a recommendation system based on a mobile application designed to help people with heart disease, families of people with heart disease, and the general public who are interested in a heart disease diet to get recommendations for diet menus that suit the nutritional needs of people with heart disease. To create a good application, we need a good user interface as well. So that the application prototype needs to be evaluated for its feasibility in terms of the user interface by doing usability testing. In this study, the method used is the System Usability Scale (SUS) which gets an average SUS score of 75.33333. The assessment criteria in the Acceptability Ranges include the Acceptable level, the Grade Scale including class B, and the Adjective Ratings including Excellent. So that the application of the "HeartReco" heart disease diet menu recommendation is good/worthy to be developed to the next stage.